Phosphate removal from wastewater using electric arc furnace slag - Ooi, Jing Lin, 1988-; Zaiton Abdul Majid, supervisor; Fakulti Sains (2011)
Project paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2011